KEPADATAN POPULASI KUMBANG TANDUK Oryctes rhinoceros L. (COLEOPTERA : SCARABAEIDAE) PADA TANAMAN SAWIT DI KANAGARIAN SURANTIH KECAMATAN SUTERA KABUPATEN PESISIR SELATAN - handayani, Wiwit fitri; Jasmi, Jasmi; safitri, Elza (STKIP PGRI Sumbar, 2014)
ABSTRACT The role of insects beneficial or detrimental. One of the harmful insects that horn beetle (Oryctes rhinoceros L.). Horn beetle attack is one of the plants palm trees. Horn beetle attack oil plant on productive phase by way of gnawing and sucking fluids and eat the contents of the palm fruit. Horn beetle attack can cause cavities and palm fruit becomes damaged so as to result in a decrease in crop production . The purpose of this study was to determine the population density of horn beetle Oryctes rhinoceros L. (Coleoptera : Scarabaeidae) on palm trees in the District Surantih Kanagarian Silk South Coastal District. This study was conducted in September 2013 with a descriptive survey method is the direct collection of the existing horn beetle research sites. Sampling was done at night from 19:00 to 21:00 oclock pm with a random sampling technique to plant oil palm. Sampling is done directly by hand and then using tweezers tool samples that have been obtained in the field is inserted into the bottle collection that already contains alcohol and taken to the laboratory for identification Andalas University. Based on the results, the characteristics of beetle horn shape or elongated ovoid, dark brown, shiny, has a horn on the head, the body length of 42-45 mm, 3-5 mm long horn and width 16-21 mm, male beetles have longer horns than the female beetles, beetle females have hair on the tip of the abdomen while the male beetle does not have hair on the tip of the abdomen, horn beetle population densities obtained on palm trees in the District Surantih Kanagarian Silk South Coastal District is 0,5 head/trunk and intensity categorized attacks still below the threshold .